Relationship Quality in Online Marketing From the Philosophy of Science Perspective - Estetika Iman Saputri; Mugi Harsono (Jurnal Indonesia Sosial Teknologi, 2024)
This study explores the concept of relationship quality from the philosophy of science. The study focuses on the scientific paradigm that forms the foundation and core of research. Relationship quality emphasizes the importance of strong relationships in creating value for customers and maintaining their loyalty in the long term. Marketing has evolved from a product-oriented approach to a customer relationship-oriented approach, making relationship quality the key to competitive advantage. This study examines the philosophical perspective of science concerning ontology, epistemology, methodology, and axiology. The research method employed is a literature review to explore the development of research on relationship quality. Mapping previous research from 2016 to 2023 provides insights into the latest trends related to the concept of relationship quality in the domain of online marketing. The results identify information sharing, online relationship bonds, and customer experience as antecedent variables of relationship quality, while the consequence variables include the intention to co-create brand value. This study proposes a research model of relationship quality from these antecedent and consequence variables.